Description of morphological changes in neurons and endothelial cells of CA1-area of hippocampus in rats with alloxan-induced hyperglycemia under application of nootropic drugs. - Zhylyuk, V. I.; Mamchur, V. I. (Морфологія / Morphologia / Morfologìâ, 2012)
Using neuromorphometry analysis differences in the effects of nootropic drugs on morphology and function of neurons and endothelial cells of hippocampus, content of RNA, content of apoptotic and destructive neurons were examined in white rats with chronic alloxan-induced hyperglycemia. It has been found that diabetes in rats is accompanied by specific morphological and functional changes and activation of apoptosis in neurons of the CA1-area in hippocampus, which may be related to disturbance of local blood flow due to endothelial damage. N-carbamoyl-methyl-4-phenyl-2-pyrrolidone (entrop), N-phenylacetyl-L-prolylglycine (noopept), pramiracetam, cerebrocurin and citicoline show protective effects on neurons and endothelial cells, which are much larger in force than effects of ginkgo biloba extract, piracetam and pentoxifylline. This protective activity is characterized by reducing the number of apoptotic and destructive neurons in hippocampal CA1-area, increasing the density of functioning nerve and endothelial cells, activation of RNA biosynthesis in the neurocytes and endothelial cells.